Determinan keputusan pembelian di Shopee: online customer review, brand image dan promosi - Ilham Bima; Iva Nurdiana Nurfarida; Endi Sarwoko (MBR (Management and Business Review), 2021)
The purpose of this research is to investigate the factors that influence purchasing decisions at Shopee Ninetysix.id seen from online customer reviews, brand image, and promotions. The method used is quantitative with an accidental sampling technique on 112 Ninetysix.id customers. Data collection uses Google Form to fill out the questionnaire, then analysis uses Multiple Linear Regression. The results of the study reveal that purchasing decisions at Shopee are due to considering the online customer reviews of previous consumers, also considering the brand image of the product to be purchased. Promotion is no longer a factor that consumers consider when making purchases at Shopee. Future research can develop a comparative study of purchasing decisions between Shopee and other marketplaces such as Tokopedia or Bukalapak.